Effect of interface treatment on the flexural performance of existing RC bridge beams strengthened with UHPC - Song, Jianping; Li, Baojun; Kong, Lingcai; Qin, Dafan; Zhu, Chao; Kuang, Yang; Shan, Aicheng (Frontiers in Materials, 2024)
As one of the most innovative cement-based materials, ultra-high performance concrete (UHPC), with excellent durability and mechanical properties, has been widely used in strengthening existing bridges.In this study, in-situ four-point bending tests were carried out to investigate the flexural behavior of precast reinforced concrete (RC) hollow slab beams in service for 15 years strengthened with UHPC.Among them, three hollow slab beams were strengthened with UHPC, and the interface treatment was chiseling, planting rebars, and a combination of chiseling and planting rebars, respectively. The remaining one without any strengthening treatment was used as the control specimen. To evaluate the enhancement effect of different interface treatments on UHPC-strengthened beams, the cracking load, ultimate load, crack development and failure modes of UHPC-strengthened beams were analyzed.Results indicated that the stiffness, deflection capacity and flexural capacity of UHPC-strengthened beams was significantly improved. Meanwhile, the stiffness of UHPC-strengthened beams in the predamage stage was increased by 49% -94%, when compared with the unstrengthened beam.Correspondingly, the ultimate flexural capacity was increased by 29% -38%. The interface chiseling treatment was more favorable to enhance the deformation capacity of UHPC-strengthened beams. The interface planting rebar treatment was more favorable to enhancing the ductility of UHPC-strengthened beams. The crack development was effectively suppressed by the interface chiseling and planting rebars together. This contributes to a higher load capacity reserve for UHPC-strengthened beams. The bearing capacity under serviceability limit state of the UHPC-strengthened beams was increased by 1.25, 2, and 2.5 times through the interface treatments of chiseling, planting rebars, and a combination of both, respectively.